2020
DOI: 10.1177/1078155220922598
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, preventive practices and perceived barriers to screening about colorectal cancer among university students of newly merged district, Kpk, Pakistan – A cross-sectional study

Abstract: Introduction Colorectal cancer is the third most common type of cancer in the world and in Pakistan it ranks at fifth position. The present study was conducted to evaluate the knowledge, attitude, preventive practices and perceived barriers to screening about colorectal cancer among university students. Method A cross-sectional study was conducted after developing a self-administered questionnaire among the university students of newly merged districts of Kpk, Pakistan Result A total of 302 students (232 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
3
19
3
Order By: Relevance
“…This might be due to the difference in socio-economic status and organizational policies and access to the information-related to CRC, and its risk factors. The result of this study is also lower than the finding of studies conducted in Pakistan [53] which is 66.6%. This discrepancy might be due to differences in the study population in which the Pakistan study included only young university students and might be getting awareness through the educational curriculum.…”
Section: Awareness Of Participants Toward Colorectal Cancercontrasting
confidence: 91%
“…This might be due to the difference in socio-economic status and organizational policies and access to the information-related to CRC, and its risk factors. The result of this study is also lower than the finding of studies conducted in Pakistan [53] which is 66.6%. This discrepancy might be due to differences in the study population in which the Pakistan study included only young university students and might be getting awareness through the educational curriculum.…”
Section: Awareness Of Participants Toward Colorectal Cancercontrasting
confidence: 91%
“…Results of five studies showed fear of the painful medical procedures [11,20,38,39,41]. Fear of tumour detection and test result subsequent fear of developing CRC and fear of complications cause ignorance of screening [11,22,29,33,41,43,46,49]. Of the included studies, 51.6% reported fear of painful medical procedures as perceived barriers [11].…”
Section: Fears Of Result Fear Of Proceduresmentioning
confidence: 99%
“…CRC and fear of complications cause ignorance of screening [ 11 , 22 , 29 , 33 , 41 , 43 , 46 , 49 ]. Of the included studies, 51.6% reported fear of painful medical procedures as perceived barriers [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were performed in the study by Rocke et al, in which only half of respondents considered the development of colorectal cancer equally dangerous in both genders 20 . Some analysis concerning CRC con rmed that women were more knowledgeable than men 20,21,32,33 . Recent studies suggest that a higher proportion of women is diagnosed with right-sided CRC, at a more advanced stage 34 .…”
Section: Discussionmentioning
confidence: 99%